2014
DOI: 10.3892/or.2014.3022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the HIF-1α and NF-κB loop on epithelial-mesenchymal transition and chemoresistance induced by hypoxia in pancreatic cancer cells

Abstract: Abstract. Hypoxia is a microenvironmental factor which plays a critical role in tumor development and chemoresistance. Epithelial-to-mesenchymal transition (EMT) induced by hypoxia is one of the critical causes of treatment failure and chemoresistance in different types of human cancers. Stabilization of the hypoxia-inducible factor-1α (HIF-1α) transcription complex, caused by intratumoral hypoxia, promotes tumor progression and chemoresistance. Previous evidence suggests that hypoxia can also activate nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Suppression of HIF-1α using siRNA resulted in an enhanced efficacy of gemcitabine in the treatment of several pancreatic tumour cell lines [40, 41]. Nevertheless, in line with our results, knockdown of HIF-1α has also been reported to have no effect on the sensitivity of pancreatic PANC-1 cells when treated with gemcitabine under hypoxic conditions [35].…”
Section: Discussionsupporting
confidence: 76%
“…Suppression of HIF-1α using siRNA resulted in an enhanced efficacy of gemcitabine in the treatment of several pancreatic tumour cell lines [40, 41]. Nevertheless, in line with our results, knockdown of HIF-1α has also been reported to have no effect on the sensitivity of pancreatic PANC-1 cells when treated with gemcitabine under hypoxic conditions [35].…”
Section: Discussionsupporting
confidence: 76%
“…Experimental studies have revealed that the stabilization of HIF-1␣ by hypoxia can directly or indirectly stimulate the expression of several E-box-binding transcription factors known to regulate EMT, including TWIST1, ZEB2, and SNAIL (64,90,121,124), while discrepancies among models suggest context-dependent events. Additionally, under some circumstances, hypoxia may sustain major CSC and EMT-regulatory pathways, such as TGF-␤, nuclear factor-B, and Notch signaling pathways (16,69,96,122,123). Recently, a new concept, that EMT can modulate the antitumor immune response, has emerged.…”
Section: Effect Of Hypoxic Stress On Tumor Target Plasticitymentioning
confidence: 99%
“…NF-κB is a critical transcriptional activator of HIF-1α and basal nuclear factor-κB activity is required for HIF-1α protein accumulation under hypoxia (Taylor et al, 2009). Moreover, a hypoxia-dependent transcriptional Hanaa Hibishy Gaballah et al upregulation of hypoxia-inducible factor-1α by nuclear factor-κB was reported in several types of cancer (Yoshida et al, 2013), stimulating epithelial to mesenchymal transition (Cheng et al, 2014), thus promotinralg tumor growth and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%